(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Metastasis, which occurs when cancer cells disseminate from the primary tumor site to other parts of the body, is the primary cause of mortality in patients, and the recurrence of multiple metastatic tumors is an obstacle to eliminating cancer. Recent clinical studies demonstrated that patients who respond to immunotherapy have longer survival rates with lower metastatic relapse, suggesting that immunotherapy may be one of the solutions to overcome cancer metastasis. Indeed, various host immune cells not only shape the tumor microenvironment but also participate in multiple stages of metastasis. Therefore, to improve clinical outcome, it is critical to understand the immunological events associated with tumor development and progression. In this article, we summarize those events that are involved in tumor progression and discuss immunotherapies that can potentially target cancer metastasis.